Level‐set‐based method for designing novel brushed synchronous machines. (10th January 2023) - Ristagno, Baptiste; Devornique, Geoffrey; Giraud, Dominique; Fontchastagner, Julien; Netter, Denis; Takorabet, Noureddine; Labbe, Nicolas
Abstract: Nowadays, research on electromagnetic devices increasingly focuses on multiphysics three‐dimensional complex systems. However, this kind of simulations require huge computational resources and consequently very high CPU time. Ristagno et al. proposed a level‐set based method allowing meshing step savings in any iterative processes (as movement modeling or optimization processes). The level‐set method lies in implicit description of moving fronts as described in the study by Osher et al. (1988). Inspired by Räisänen et al., all physical parameters (material properties, supply or armature movement) are implemented by projection of mathematical functions. In this paper, the authors proposes to study and design a new kind of mechanical commutator for DC machines thanks to this coupled method. Indeed, there is a renewed interest in DC machines because they can be suitable for small mobilities. To be noted, small mobility concerns all kind of vehicles (2 wheels–4 wheels–autonomous vehicles such as drones) that have speeds below 50 km/h. However, specifications for traction applications are difficult to achieve for such a rustic machine and requires some modifications. That is why, inspired by usual synchronous machine, the commutator has been redesigned to obtain expected theoretically signal waveform. Furthermore, numerical coupled simulations have been used to design both machine and supply simultaneously. This work has led to the manufacture of a proof of concept and preliminary results are very promising.